The design and interpretation of laboratory assays measuring mosquito transmission of Plasmodium. - Sinden, R; Blagborough, A; Churcher, T; Ramakrishnan, C; Biswas, S; Delves, M (2012)
Since 2010 two global reviews of malaria research have recognized that local elimination and eradication of Plasmodium parasites are key drivers for further experimentation. To achieve these ambitious objectives it is universally recognized we must reduce malaria transmission through the mosquito vectors. A plethora of new laboratory assays are being developed to interrogate malaria transmission from the gametocyte to the sporozoite stage: assays that augment well-established field protocols to determine the entomological inoculation rate. However, the diverse readouts of these assays are not directly comparable. Here we attempt to identify the utility of each assay and provide rational frameworks by which to compare the impacts recorded by the diverse methodologies.